2020
DOI: 10.1111/bjd.19017
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo confocal microscopy: revolution in fast pathology in dermatology

Abstract: Summary Confocal microscopy with in vivo and ex vivo modalities has been used in the evaluation of skin cancer and other dermatological disorders. Recent developments in ex vivo confocal microscopy allow for faster pathology assessment with greater accuracy by the visualization of cellular and architectural details, similarly to standard pathology, in either paraffin‐embedded or frozen samples. They include the possibility of multimodal confocal microscopy using different lasers and fusion images. New staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 78 publications
2
52
0
Order By: Relevance
“…Despite its somewhat nonspecific staining behavior, AO has been successfully employed as a nuclear staining agent to imitate hematoxylin in a rapidly growing number of studies on confocal imaging of fresh tissue [24]. However, the limitations of AO include staining of non‐nuclear structures and presence of unbound dye in the dermis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its somewhat nonspecific staining behavior, AO has been successfully employed as a nuclear staining agent to imitate hematoxylin in a rapidly growing number of studies on confocal imaging of fresh tissue [24]. However, the limitations of AO include staining of non‐nuclear structures and presence of unbound dye in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…While dermal fibers can be visualized because of their autofluorescence at 488 nm (vs 638 nm) in control unstained tissues, accentuation of dermal fibers (collagen, elastin) in AO images was prominently visible after staining, suggesting some degree of nonspecific staining. Histology correlation studies, as well as prospective clinical investigations to evaluate diagnostic accuracy (sensitivity, specificity, positive and negative predictive value), would be needed to definitively test and prove DRAQ5's enhanced diagnostic value relative to that of AO [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the epidermis of the eyelid is thinner than the rest, and it has a unique meibomian gland mechanism. Ex vivo CLSM has been used for rapid identification of skin tumor slices, but the diagnosis of the tumor tissue has not been used for eyelid tumors [ 26 ]; so, it is a promising research direction. The purpose of this study is to explore the imaging of the eyelid structure of normal people.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work indicated a sensitivity and specificity of 88% and 99%, respectively [ 7 ], and a more recent diagnostic test of accuracy study (753 fresh Mohs specimens) reported a sensitivity of 79.8% and a specificity of 95.8%, when compared with frozen section histopathology [ 11 ]. Recent studies have shown that FCM images can be digitally coloured to appear similar to H&E sections [ 12 ]. Peters et al reported that BCC was identified with a 73% sensitivity and a 96% specificity in digitally coloured FCM images of 544 fresh specimens from 148 BCC excisions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%